2-Hydroxy-4-Ethoxy-5-Bromopropiophenone Oxime as an Analytical Reagent for Cu(II) - Desai, B.D.; Desai, K.K. (Asian Journal of Chemistry, 2010)
2-Hydroxy-4-ethoxy-5-bromopropiophenone oxime (HEBPO) was developed as a new analytical reagent for the gravimetric estimation of Cu(II). In pH range 3 to 8 the reagent gives a buff coloured precipitate with Cu2+. Job's method and Yoe Jones' mole ratio method revealed that the stoichiometry of the complex is 1 : 2 metal : ligand. The Beer law is obeyed up to 101.90 ppm of Cu2+. The molar absorptivity and the Sandell's sensitivity at 420 nm were found to be 1.725 X 102 Lit mol-1 cm-1 and 0.368 μg/cm2 respectively. The stability constant of Cu(II)-HEBPO complex is found to be 3.154 X 108. Gibb's free energy change for complex formation reaction was found to be -11.624 kcal/mole. The reagent can be used for the analysis of brass.